AB0099 Overexpression of uPAR in Fibroblast-like Synoviocytes Promotes Angiogenesis in Patients with Rheumatoid Arthritis. (15th July 2016) - Yan, L.; Feng, P.Y.; Ting, W.Y.; Meng, L.
Abstract : Background: Urokinase-type plasminogen activator receptor (uPAR), is a multi-functional receptor on cell surface, widely present in endothelial cells, fibroblasts, and a variety of malignant cells. Our previous studies have suggested that expression of uPAR is higher in patients with rheumatoid arthritis (RA) compared to osteoarthritis (OA) and the traumatic patients. Objectives: Our objective was to investigate the promoting-angiogenesis effects of uPAR in fibroblast-like synoviocytes from patients with rheumatoid arthritis (RA-FLSs). Methods: Chemically synthesized small interference RNA (siRNA) specifically targeting the uPAR gene was transfected into RA-FLSs by cationic liposome and the cell supernatants from uPAR gene-silenced RA-FLSs were extracted to cultivate the EA.hy926 (a human endothelial cell line). Transwell and tubule formation assays were used to explore the influence of RA-FLSs uPAR on EA.hy926 angiogenesis. Results: EA.hy926 cells treated with conditioned medium of uPAR-siRNA RA-FLSs had a worse migrating ability and tubule formation effects, for they had only about 38% transmembrane cells and the average number of complete tubular structures decreased to 38.2%, relative to the transfection reagent control group (*P<0.05). Conclusions: uPAR in RA-FLSs affects neoangiogenesis of synovial tissues in patients with RA, which imply that targeting uPAR and its downstream signal pathway may provide beneficial therapeutic effects on RA. References: Noh H, Hong S, Huang S. Role of urokinase receptor in tumor progression and development. Theranostics. 2013;3(7):487–95. Ferraris GM, Sidenius N. Urokinase plasminogen activator receptor: a functional integrator of extracellular proteolysis, cell adhesion, and signal transduction. Seminars in thrombosis and hemostasis. 2013;39(4):347–55. Yoo SA, Kwok SK, Kim WU. Proinflammatory role of vascular endothelial growth factor inthe pathogenesis of rheumatoid arthritis: prospects for therapeutic intervention. Mediators of inflammation. 2008;2008:129873. Disclosure of Interest: None declared